2021
DOI: 10.1038/s41598-021-86440-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic effects between topical 8-oxo-2′-deoxyguanosine and corticosteroid in ocular alkali burn model

Abstract: We compared the therapeutic effects of topical 8-oxo-2′-deoxyguanosine (8-oxo-dG) and corticosteroid in a murine ocular alkali burn model. (n = 128) The corneal alkali burn model was established by applying 0.1 N sodium hydroxide (NaOH), followed by treatment with 8-oxo-dG, 0.1% fluorometholone (FML), 1% prednisolone acetate (PDE), or phosphate-buffered saline (PBS) twice daily. One week later, the clinical and histological status of the cornea were assessed. Transcript levels of inflammatory cytokines and nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…We speculate that the inhibitory effects of RCI001 on Rac1 mediate suppression of the NLRP3 inflammasome/IL-1β pathway, implicated in ROS generation via NADPH oxidase or TLR-related NF-κB activation ( 21 , 23 ) ( Figure 7 , presumed mechanism of RCI001 on the NLRP3 pathway). RCI001 was shown to modulate the activation of MAPK, ERK, and STAT pathways in the ocular alkali burn model ( 5 ). In the present study, we observed a discrepancy in the expression of Rac1, NLRP3, and caspase-1 between qPCR and western blotting ( Figures 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We speculate that the inhibitory effects of RCI001 on Rac1 mediate suppression of the NLRP3 inflammasome/IL-1β pathway, implicated in ROS generation via NADPH oxidase or TLR-related NF-κB activation ( 21 , 23 ) ( Figure 7 , presumed mechanism of RCI001 on the NLRP3 pathway). RCI001 was shown to modulate the activation of MAPK, ERK, and STAT pathways in the ocular alkali burn model ( 5 ). In the present study, we observed a discrepancy in the expression of Rac1, NLRP3, and caspase-1 between qPCR and western blotting ( Figures 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corneal epithelial integrity was evaluated by administering 1 drop of 3% Lissamine Green B (Sigma-Aldrich) to the inferior lateral conjunctival sac and photographed using a Dino-Lite digital camera (Dino-Lite Pro, AnMo Electronics Corp, Hsinchu, Taiwan). Evaluation of corneal epithelial integrity and corneal clarity were performed by three blinded observers by the scoring systems as described elsewhere ( 5 , 17 ). Corneal epithelial integrity was scored using the following scale of 0 to 4 based on the intensity of corneal epithelial defects: 0 = no epithelial defect, 1 = less than 25% epithelial defect, 2 = 25–50% epithelial defect, 3 = 50–75% epithelial defect, and 4 = more than 75% epithelial defect ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations